Implementasi Akuntansi Sosial Sebagai Bentuk Tanggungjawab Sosial Perusahaan - Valeria Putri Olivia (LPPM UBP, 2023)
Establishment of a company does not only have responbility to present financial report with accounting method but also pay attention for social environment towards external and internal affect to stakeholders for make a decisions. The research process was carried out in an observational and exploratory manner using the literature review method. The population in this study is all research and studies related to the social accounting and corporate responsbility. The result is social accounting provides ouput reporting resposbility company to the social environment. It takes awareness in operating corporate activity not just for profit but takes a community environment, so not gonna take controversy and other problems.